Graphene chemistry : theoretical perspectives - Jiang, De-en, 1975-; Chen, Zhongfang, 1971- (John Wiley & Sons Inc., 2014)
"The aim of this book is to deliver a comprehensive view of graphene chemistry from various perspectives out of theoretical and computational investigations"--